Global system for mobile communication based domestic electrical load control using arduino uno - L. Velusamy; S. Salimin; S. N. M. Rozi; M. N. Abdullah; N. H. Radzi; S. A. Jumaat; A. F. M. Noor; R. Hamdan (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a wireless operation to switch on and off the load such as light, fan and power socket by sending messages via smartphone. The proposed project is focused on usage of the global system for mobile communication (GSM) protocol, which enables the user to control loads away from targeted area using the frequency bandwidths. The concept of serial communication and Uno microcontroller-commands are being applied towards development of the GSM based domestic electrical load control using Arduino UNO system. Besides that, the existing electrical switches that control the load manually is not being removed and this gives a safer control over the switches with low voltage usage technique. This system is designed to control electrical devices throughout the house with easy installation process, ease of use and cost effective design and implementation. Additionally, the system has several possibility to help satisfy the needs of the elderly and the handicapped at houses. Prototype of GSM based domestic electrical load control using Arduino UNO was implemented and successfully tested with maximum of five loads such as light, fan and power sockets.